2016
DOI: 10.1190/geo2015-0524.1
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of long-period long-duration seismic events detected during hydraulic fracturing

Abstract: Long-period long-duration (LPLD) seismic events are low-amplitude tremor-like seismic signals that have been observed in some microseismic monitoring data sets acquired during hydraulic fracturing operations. LPLD events have been interpreted to be associated with slow-slip along preexisting fractures which are presumed to have either high clay content or be misaligned with respect to the current day principal stress directions. However, a recent study shows that regional earthquakes, when recorded on vertical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…However, Zecevic et al . [] analyzed the USArray data and suggested that small regional earthquakes could be the cause of some of the LPLD events observed by Das and Zoback [, ]. This suggestion aligns with the study by Caffagni et al .…”
Section: Introductionsupporting
confidence: 77%
See 4 more Smart Citations
“…However, Zecevic et al . [] analyzed the USArray data and suggested that small regional earthquakes could be the cause of some of the LPLD events observed by Das and Zoback [, ]. This suggestion aligns with the study by Caffagni et al .…”
Section: Introductionsupporting
confidence: 77%
“…Das and Zoback [2011, 2013a, 2013b associated the LPLD events in the Barnett Shale with superposition of slow shear-slip events on relatively large faults due to high fluid pressure or high clay content. However, Zecevic et al [2016] analyzed the USArray data and suggested that small regional earthquakes could be the cause of some of the LPLD events observed by Zoback [2013a, 2013b]. This suggestion aligns with the study by Caffagni et al [2015], who showed that regional earthquakes in central Alberta in Canada were recorded as LPLD events on downhole seismic arrays for monitoring hydraulic fracturing.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations